Alternativas pedagogicas de nefoanálisis con imágenes satelitales a través de herramientas manuales y digitales para la estimación de áreas nubosas en Venezuela (Gaceta Técnica, 2018)
Recently, there has been progress in space technology, becoming this progress on a key piece in the study and monitoring of the main environmental parameters from Earth observation platforms. This process is supported by a large number of passive sensors that capture the spectral, spatial and temporal variations of electromagnetic waves emitted and / or reflected by each material element of nature, generating images on land then analyzed using specific softwares and Remote Sensing techniques. This field research describes procedures for nephanalysis or cloud analysis through visible images transmitted from the satellite GOES by two tools: the call Dot Matrix and AutoCAD. It aims to create alternatives that serve as background and innovative contribution in the area of Climate Science to complement the diagnosis, prognosis and modeling of atmospheric dynamics, but primarily as a teaching alternative in physics. Four images obtained at the Department forecast SERMETAVIA-Barquisimeto were used. They were selected according to the following criteria: Satellite Source, Image Type, Geo- referential Scale and Multitemporal Registration. These were processed with the tools above, achieving estimate the cloud area of Venezuela, yielding values close between AutoCAD and Dot Matrix areas. It can be said that this last tool can be used as a technique to estimate cloudy areas and at the same time as a educational resource for teaching contents of Physics and Electromagnetism, Optics, Modern Physics and others involved in the physical principles to generate a satellite image
Keywords: remote sensing; satellite imagery; GOES satellite; nefoanalysis